A systematic analysis for disease burden, risk factors, and trend projection of Alzheimer’s disease and other dementias in China and globally - Siyu Liu; Daoying Geng (PLoS ONE, 2025)
Background This study aims to provide improvement directions for aging societies by analyzing the disease burden, risk factors and trend forecasts of AD and other dementias (ADD) in China and globally from 1990 to 2021. Methods Data sourced from Global Burden of Disease 2021. We extracted indicators of disease burden and risk factors for ADD in people aged 40 years and older, including incidence, prevalence, deaths, disability-adjusted life years, years lived with disability and years of life lost. The annual percent change and average annual percent change over the past 32 years were analyzed by Joinpoint regression. Decomposition analysis was used to clarify the contribution of aging, population and epidemiological change. The directions of deaths and incidence in China and globally were predicted using ARIMA model for the next 15 years. Results The disease burden of ADD in China is heavier than in most countries and regions. By 2021, China’s disease burden has increased by three times, while the global disease burden has doubled. Females bear more burden but face lower mortality. Population growth is the main reason for the burden. Smoking, high fasting plasma glucose and high body-mass index are the three major risk factors, among which high fasting plasma glucose occupies a dominant position. Conclusion The disease burden of ADD in China and globally is increasing daily and will remain high in the future. It is urgent to introduce some effective intervention measures to prevent such diseases as early as possible.